Diaspididae (Hemiptera, Coccoidea) in sori of two fern species - Santos, Marcelo Guerra; Wolff, Vera Regina dos Santos (EntomoBrasilis, 2015)
Abstract. This note reports the presence of two scale insects species Hemiberlesia palmae (Cockerell) and Pinnaspis strachani (Cooley) (Coccoidea, Diaspididae), associated respectively with Asplenium serratum L. (Aspleniaceae) and Niphidium crassifolium (L.) Lellinger (Polypodiaceae). It is the first record of a fern species as host plant of Hemiberlesia palmae (Cockerell). In both fern species, the diaspidids were found nearby the sori. Duas Espécies de Cochonilhas (Hemiptera: Diaspididae) Associadas com Soros de Samambaias Resumo. A presente comunicação relata a presença de duas espécies de cochonilhas Hemiberlesia palmae (Cockerell) e Pinnaspis strachani (Cooley) (Coccoidea, Diaspididae), associadas respectivamente com Asplenium serratum L. (Aspleniaceae) e Niphidium crassifolium (L.) Lellinger (Polypodiaceae). É o primeiro registro de uma samambaia como planta hospedeira de Hemiberlesia palmae. Nas duas espécies de samambaias, os diaspidídeos encontravam-se concentrados principalmente ao redor dos soros.